Influence of irofulven, a transcription-coupled repair-specific antitumor agent, on RNA polymerase activity, stability and dynamics in living mammalian cells. - Escargueil, A; Poindessous, V; Soares, D; Sarasin, A; Cook, P; Larsen, A (2008)
Transcription-coupled repair (TCR) plays a key role in the repair of DNA lesions induced by bulky adducts and is initiated when the elongating RNA polymerase II (Pol II) stalls at DNA lesions. This is accompanied by alterations in Pol II activity and stability. We have previously shown that the monofunctional adducts formed by irofulven (6-hydroxymethylacylfulvene) are exclusively recognized by TCR, without involvement of global genome repair (GGR), making irofulven a unique tool to characterize TCR-associated processes in vivo. Here, we characterize the influence of irofulven on Pol II activity, stability and mobility in living mammalian cells. Our results demonstrate that irofulven induces specific inhibition of nucleoplasmic RNA synthesis, an important decrease of Pol II mobility, coupled to the accumulation of initiating polymerase and a time-dependent loss of the engaged enzyme, associated with its polyubiquitylation. Both proteasome-mediated degradation of the stalled polymerase and new protein synthesis are necessary to allow Pol II recycling into preinitiating complexes. Together, our findings provide novel insights into the subsequent fate of the stalled RNA polymerase II and demonstrate the essential role of the recycling process for transcriptional reinitiation and viability of mammalian cells.